ความสอดคล้องระหว่างมาตรา 43 วรรคหนึ่งกับมาตรา 67 วรรคสองในรัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2550 : กรณีศึกษาการจัดการขยะมูลฝอยชุมชน - เอกราช มาเจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The objective of this thesis is to study the problem of the interpretation and application of Article 67 Paragraph 2 in the case that it affects the freedom of individual to conduct the business or occupation of management of community waste, which is the public service assigned or licensed from the local administrative organization to serve, in order to study the balance of the public interests and the protection of the right of community and freedom of individual to conduct the business or occupation of management of community waste. After studying the principle of proportionality, the principle of the legal certainty, the principle of interpretation of a written Constitution to protect the people’s rights and freedoms, spirit of Article 67 and Article 43, the legislation relating to management of community waste, the concerned ruling of the Judiciary including the problem of the local administrative organization in management of the community waste, there are 3 main problems; the uncertainty of the interpretation and application of Article 67 Paragraph 2, the uncertainty of whether the community waste management is in the scope to comply with Article 67 Paragraph 2, and the uncertainty of legality of rules under Article 67 Paragraph 2. Therefore, in case the interpretation of Article 67 Paragraph 2 affect the freedom of individual to conduct the business or occupation of management of community waste, the principle of proportionality and the principle of the legal certainty should be applied to create balance of the protection of the community’s right and freedom and the management of community waste of the local administrative organization.